Consideration about moral accomplishment: a necessity in today’s world - Tutuianu, Iulia (Journal of Education Culture and Society, 2020)
Unlike in the atheist existentialism, the Christian one finds the individual in palpable situations, seen as opportunities in the process of personal accomplishment. The existentialism is not a quietude philosophy, but it asks for permanent effort. The religious man has a meaning, a purpose, The Encounter with Absolute, his entire life being part of Propedeutica. He replaces the anguish with hope, with the joy of being closed to God which occurs in each moment when we are aware that we follow our destiny.